2010
DOI: 10.4103/0019-509x.64726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of colposcopy vs cytology as secondary test to triage women found positive on visual inspection test

Abstract: Colposcopy is a good sensitive test for the detection of CIN and can be considered as a secondary testing tool to triage women found positive on VIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Our study also showed that a VIA nurse colposcopist Swede score of 8 or above had parallel high specificities of CIN2+ as the Swede score of the doctors. These results are comparable to CIN2+ specificities in Swede score trials by doctors from both high-resource11 12 and low-resource settings 1314…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our study also showed that a VIA nurse colposcopist Swede score of 8 or above had parallel high specificities of CIN2+ as the Swede score of the doctors. These results are comparable to CIN2+ specificities in Swede score trials by doctors from both high-resource11 12 and low-resource settings 1314…”
Section: Discussionsupporting
confidence: 60%
“…Colpscopy may also be used for primary screening in low-resource settings, especially when using the Swede score systematic colposcopy system, where the total score gives an indication of the severity of the visual impression of the cervix 11–15. However, the limited access of doctors and the limitations of stationary colposcopes (heavy, requires an electrical grid and technical support) are reasons why screening colposcopy has not reached widespread use in rural areas with poor infrastructure 11…”
Section: Introductionmentioning
confidence: 99%
“…Histopathology findings were reported as benign in 81.6%, CIN I in 5.8% of cases, CIN II in 2.9% of cases, CIN III in 2.6% of cases, and invasive carcinoma in 2.9% of cases. The estimates of sensitivity for low- and high-threshold colposcopy were 58% and 74.5%, respectively, and those of specificity were 57.5% and 92.9%, respectively [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] An earlier Mumbai study reported sensitivity of 67.9%, 62.3%, and 57.4% of cytology at the threshold of ASCUS+, LGSIL+, and HGSIL, respectively, with CIN 2+ histopathology as the gold standard on all VIA-positive women. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] In the Mumbai study, the specificity of pap as triage test was 99.4%, 98.0%, and 96.8% to detect HGSIL+, LGSIL+, and ASCUS+ with histopathology CIN 2+ as the gold standard on VIA-positive women. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%